Threats to the Innovative Security of Regional Development in a Digital Society - Golova, Irina Markovna; Sukhovey, Alla Filippovna (Economy of Regions, 2018)
This article discusses the problems of ensuring the innovative security of regional development in a digital society. The hypothesis of the study is to suggest that the emergence of digital technical and economic paradigm is accompanied by innovative regional development risks and introduces significant changes in the ideology and mechanisms of the territorial innovative security. We have assessed the level of the development of the digital economy and innovation in Russia using the comparative analysis. We have developed a methodological approach based on rating. The approach allows assessing the level of favourable conditions in the regions of Russia for the formation and development of the high-tech sector of the economy. We have suggested the definition of innovative security, which is formulated in accordance with modern views on how to achieve the sustainable development of territories and maintain their competitiveness in the new reality. We have revealed the impact of specific factors of the digital economy on the global and regional innovative processes. The research reveals basic problems and justifies the most promising options for Russia to build the strategy of innovative security. The paper shows that, in the Russian Federation, the absolute priority for innovation security is the development of innovation ecosystem, which would be adequate to the challenges of digital society. This innovation ecosystem should be capable to achieve acceptable (considering the competition in global markets) parameters for the development of science, the high-tech manufacturing sector, and higher education. We have proved that the establishment of the innovation ecosystem of the country is strategically important to start with the regions, holding leading positions on science development, innovative capacity and high-tech industries. Calculations are made using official statistics and allow to define with reasonable objectivity spatial priorities for the innovative security strategy of the country. We have formulated the directions for improving public policies as a mandatory condition for increasing the innovative security of regional development. The results of this research can be used to elaborate a strategy of innovative development as well as to address practical issues of managing innovation processes of the territories and to enhance the sustainability of regional development.